2009
DOI: 10.1038/modpathol.2009.117
|View full text |Cite
|
Sign up to set email alerts
|

Delay to formalin fixation effect on breast biomarkers

Abstract: Delay to formalin fixation may invalidate hormone receptors and HER2 analyses. Invalid results of tumor markers could significantly alter the type of adjuvant therapy a patient receives and potentially impact outcome. The purpose of this study was to determine the effects of progressive delay to formalin fixation on breast cancer biomarkers. Ten palpable invasive breast cancers were resected and underwent immediate gross evaluation. For each case, the procured tumor was divided into eight parts and consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
142
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(146 citation statements)
references
References 36 publications
3
142
1
Order By: Relevance
“…Gene amplification analysis of HER2 and EGFR by FISH could not be carried out in this study except for several recent autopsy cases because of the invalid results due to the delay in formalin fixation (up to 3-4 days) of the old archived specimens resected between 1995 and 2000 [22,23]. Nevertheless, we demonstrated the following interesting findings.…”
Section: Discussionmentioning
confidence: 48%
“…Gene amplification analysis of HER2 and EGFR by FISH could not be carried out in this study except for several recent autopsy cases because of the invalid results due to the delay in formalin fixation (up to 3-4 days) of the old archived specimens resected between 1995 and 2000 [22,23]. Nevertheless, we demonstrated the following interesting findings.…”
Section: Discussionmentioning
confidence: 48%
“…They concluded that delayed fixation of modified radical mastectomy tissues likely accounted for this finding and optimal selection of patients for hormonal therapies is dependent on tissue management strategies even before formal hormonal receptor protein testing procedures. 23 Khoury et al, 24 in their study of effects of delayed formalin fixation on 10 specimens that were kept at room temperature for 0, 10, 30 min, and 1, 2, 4, 8 h before fixation, concluded that ER expression began to decline after 2 h and PR expression after 1 h of cold ischemic time. Khoury et al 24 also reported that at 8 h of cold ischemic time, ER expression was completely negative, and they recommended that specimens be fixed ideally within 1 h of receipt, and not to be stored overnight at 4 1C.…”
Section: Discussionmentioning
confidence: 99%
“…23 Khoury et al, 24 in their study of effects of delayed formalin fixation on 10 specimens that were kept at room temperature for 0, 10, 30 min, and 1, 2, 4, 8 h before fixation, concluded that ER expression began to decline after 2 h and PR expression after 1 h of cold ischemic time. Khoury et al 24 also reported that at 8 h of cold ischemic time, ER expression was completely negative, and they recommended that specimens be fixed ideally within 1 h of receipt, and not to be stored overnight at 4 1C. Their finding was that overnight storage at 4 1C yielded similar results to leaving specimens without fixation at room temperature for 8 h. This finding is in contrast to our finding that non-refrigerated samples are affected more by prolonged cold ischemic time than refrigerated samples, whereas our finding of general decline in hormone receptor expression with increasing cold ischemic time periods is in keeping with their findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Ng et al, 2012) It only presents in a small number of cases (1-10%) and indeed re-testing of cases by some authors utilising more sensitive immunohistochemical detection systems and lower cut points suggests that at least some of these cases are double receptor positive using alternative assessment criteria (Hammond et al; Nadji et al, 2005;De Maeyer et al, 2008;Nadji, 2008). In addition hormone receptors are notoriously labile and unless tissues are fixed promptly and the cold ischaemia time between surgical removal and immersion in fixative is kept to a minimum, there is the confounding factor of receptor degradation and consequent false negative assay results (Khoury et al, 2009) All these factors need to be taken into consideration when considering the clinical relevance of the ER-PR+ result.…”
Section: Discussionmentioning
confidence: 99%